Flexor Tenosynovitis Caused by Neisseria gonorrhea Infection: Case Series, Literature Review, and Treatment Recommendations - Jain, Nirbhay; Saadat, Sean; Goldberg, Mytien (Archives of Plastic Surgery, 2023)
Neisseria gonorrhoeae is the most common sexually transmitted disease in the world and is known to cause disseminated disease, most commonly tenosynovitis. Classically, gonorrhea-associated tenosynovitis presents with concomitant dermatitis and arthralgias, though this is not always the case. N. gonorrhoeae-related tenosynovitis has become more commonly seen by hand surgeons. To aid in management, we present three cases of gonorrhea-induced tenosynovitis spanning a range of presentations with variable treatments to demonstrate the variety of patients with this disease. Only one of our patients had a positive gonococcal screening test and no patient had purulent urethritis, the most common gonorrhea-related symptom. A separate patient had the classic triad of tenosynovitis, dermatitis, and arthralgias. Two patients underwent operative irrigation and debridement, and one was managed with anti-gonococcal antibiotics alone. Though gonorrhea is a rare cause of flexor tenosynovitis, it must always be on the differential for hand surgeons when they encounter this diagnosis. Taking an appropriate sexual history and performing routine screening tests can assist in the diagnosis, the prescription of appropriate antibiotics, and potentially avoiding an unnecessary operation.
Keywords: flexor tenosynovitis; gonorrhea; nonoperative management